Prevalence and transmission of the most relevant zoonotic and vector-borne pathogens in the Yucatan peninsula: A review. - Ma Fernanda Sánchez-Soto; Osiris Gaona; Ana Laura Vigueras-Galván; Gerardo Suzán; Luisa I Falcón; Ella Vázquez-Domínguez (Public Library of Science (PLoS), 2024)
Background Habitat modification and land use changes impact ecological interactions and alter the relationships between humans and nature. Mexico has experienced significant landscape modifications at the local and regional scales, with negative effects on forest cover and biological biodiversity, especially in the Yucatan peninsula in southeastern Mexico. Given the close relationship between landscape modification and the transmission of zoonotic and vector-borne diseases, it is essential to develop criteria for identifying priority zoonoses in the south of the country. Methodology/principal findings We reviewed 165 published studies on zoonotic and vector-borne diseases in the region (2015-2024). We identified the most frequent vectors, reservoirs, and hosts, the most prevalent infections, and the factors associated with transmission risk and the anthropogenic landscape modification in urban, rural, ecotone, and sylvatic habitats. The most relevant pathogens of zoonotic risk included Trypanosoma cruzi, arboviruses, Leishmania, Rickettsia, Leptospira, and Toxoplasma gondii. Trypanosoma cruzi was the vector-borne agent with the largest number of infected vertebrate species across habitats, while Leishmania and arboviruses were the ones that affected the greatest number of people. Dogs, cats, backyard animals, and their hematophagous ectoparasites are the most likely species maintaining the transmission cycles in human settlements, while rodents, opossums, bats, and other synanthropic animals facilitate connection and transmission cycles between forested habitats with human-modified landscapes. Pathogens displayed different prevalences between the landscapes, T. cruzi, arbovirus, and Leptospira infections were the most prevalent in urban and rural settlements, whereas Leishmania and Rickettsia had similar prevalence across habitats, likely due to the diversity and abundance of the infected vectors involved. The prevalence of T. gondii and Leptospira spp. may reflect poor hygiene conditions. Additionally, results suggest that prevalence of zoonotic and vector-borne diseases is higher in deforested areas and agricultural aggregates, and in sites with precarious health and infrastructure services. Conclusions Some hosts, vectors, and transmission trends of zoonotic and vector-borne diseases in the YP are well known but others remain poorly recognized. It is imperative to reinforce practices aimed at increasing the knowledge, monitoring, prevention, and control of these diseases at the regional level. We also emphasize the need to perform studies on a larger spatio-temporal scale under the socio-ecosystem perspective, to better elucidate the interactions between pathogens, hosts, vectors, environment, and sociocultural and economic aspects in this and many other tropical regions.